Cut-off analysis of CTC change under systemic therapy for defining early therapy response in metastatic breast cancer - Deutsch, Thomas M.; Stefanovic, Stefan; Feißt, Manuel; Riedel, Fabian; Fremd, Carlo; Domschke, Christoph; Sütterlin, Marc; Schneeweiss, Andreas; Wallwiener, Markus (Cancers, 2020)
Detection of circulating tumor cells (CTC) can distinguish between aggressive and indolent metastatic disease in breast cancer patients and is thus considered an independent, negative prognostic factor. A clear decline in CTCs is observed in patients who respond to systemic therapy. Nevertheless, CTCs can decrease in patients experiencing disease progression during systemic therapy, too. This study aims to determine the differences between CTC decline in patients responding to therapy and those in whom disease is progressing. Therefore, CTC values were compared at the start and after one cycle of a new line of systemic therapy. In all, 108 initially CTC-positive patients (with ≥ 5 intact CTCs in 7.5 mL blood) were enrolled in this study and intact and apoptotic CTCs were measured via the CellSearch system. A cut-off analysis was performed using Youden's J statistics to differentiate between CTC change in the two groups. Here, 64 (59.3%) patients showed stable disease or partial response vs. 44 (40.7%) presenting disease progression. Median overall survival was 23 (range: 4-92) vs. 7 (2-43) months (p < 0.001). Median intact CTC count at enrollment was 15.0 (5-2760) vs. 30.5 (5-200000) cells (p = 0.39) and 2.5 (0-420) vs. 8.5 (0-15000) cells after one cycle of systemic therapy (p = 0.001). Median apoptotic CTC count at enrollment was 10.5 (0-1500) vs. 9 (0-800) cells (p = 0.475) and 1 (0-200) vs. 3 (0-250) cells after one cycle of systemic therapy (p = 0.01). A 50% reduction in baseline apoptotic CTC count represents the optimal cut-off to differentiate between therapy response and disease progression. An apoptotic CTC reduction of ≤ 10% is 74% specific for early disease progression.